Compressive Strength and Water Absorption of Pavement Derived from Palm Oil Eco Processed Pozzolan (EPP) Material as Partial Cement Replacement - Nurul Farhanah Mohd Kusaimi; Fazlena Hamzah; Junaidah Jai; Nurul Asyikin Md Zaki; Norliza Ibrahim (ASEAN Journal of Chemical Engineering, 2020)
Eco Processed Pozzolan (EPP) is derived from Spent Bleaching Earth (SBE) by the calcination process via heat treatment in the palm oil refining industry. EPP can be used as a partial replacement of cement as it contains a high amount of silica and has pozzolanic properties. Besides its properties, the sustainable production of EPP in the palm oil industry, abundantly available, and cheaper raw material have opened an opportunity to explore it as a cement substitute in pavement industries. This research aimed to study the properties of pozzolanic EPP and discover its potential as a partial substitute of cement in the pavement block's development. The compressive strength and water absorption of the formulated pavement block using EPP were analyzed in this study. Two sets of paving blocks were developed, namely, Set A, EPP was added as a partial replacement of the cement in pavement formulation at 20% - 90%, while in Set B, integration of EPP and Fly Ash (FA) was used as a partial replacement of the cement. The results indicated that the maximum addition of EPP into pavement formulation was 20%. The increment of EPP as a cement substitute in a formulation of more than 20% has reduced the compressive strength and increased the water absorption of the pavement. Simultaneously, the addition of FA and EPP in the formulation of hybrid pavement in Set B shows that the addition of FA has improved the compressive strength of the pavement and less water absorption was detected. The pavement’s highest compressive strength by addition of FA was 36MPa at the EPP was added of 15 – 20%. The study indicated that EPP could be used as a partial substitute of the cement, but addition of FA might require to improve pavement compressive strength.